Arthroscopic Meniscus Ramp Repair: The Shoelace Technique - Sheetal Gupta MS; Kranthi Kiran Kovvuru MS; Deepak Vashistha MS (SAGE Publishing, 2023)
Background: A "ramp lesion" is described as an injury involving the peripheral attachment of the posterior horn of the medial meniscus. Ramp lesions are associated with increased loads on anterior cruciate ligament and leads to rotatory instability of knee. During anterior cruciate ligament reconstruction, failure to identify and treat ramp lesion leads to increased forces on the reconstructed graft and residual instability which ultimately increases chances for graft failure. It is important to identify the ramp lesions by looking at the posterior compartment and repair ramp lesion. Ramp lesions are still a challenge to treat due to misdiagnosis and long learning curve of current techniques. In this technique, we are presenting margin convergence shoelace technique to repair a large ramp lesion. Indications: Isolated ramp lesions or ramp lesions associated with other ligamentous injuries. Technique Description: Through standard anteromedial and anterolateral portals, diagnostic arthroscopy is done. Using Gillquist maneuver, posteromedial compartment is visualized to look for ramp lesion. Probing is done with 18-gauge spinal needle from posteromedial aspect of knee to look for hidden lesions and extent of tear. We use 2 additional portals, low and high posteromedial portals for ramp repair. Visualizing from anterolateral portal entry is made in the posteromedial compartment; low posteromedial portal is created at the level of meniscus; 8-mm passport cannula is inserted and used as working portal; and then, high posteromedial portal is created and used as viewing portal. Visualizing through high posteromedial portal rasping of ramp lesion is done. Now with knee scorpion loaded with 2-0 fiber wire, bites are taken along posterior margin of meniscus and capsular portion of tear edges alternatively in shoelace manner from lateral to medial. Finally, compression and knot tying are done and secured with multiple half hitches. Results: Surgical repair of ramp lesions is associated with good healing, and it restores stability of knee. Follow-up of more than 2 years shows better functional outcome and reduced retear rates. Discussion/Conclusion: Currently, there are a lot of techniques described for ramp repair. We present arthroscopic ramp repair with dual posteromedial portals by shoelace technique, which is a safe, easy, and cost-effective method and gives excellent results and good healing especially in larger tears. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.